Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT. Surya Toto Indonesia, Tbk Divisi Kitchen Pasar Kemis Kabupaten Tangerang - Wahyu Hidayat; Kamsidik Kamsidik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. This study aims to determine the effect of occupational safety and health (OSH) and the work environment on employee performance at PT. Surya Toto Indonesia Tbk Kitchen Division, Pasar Kemis, Tangerang Regency. The background of this study stems from the importance of implementing occupational safety and health (OSH) and creating a comfortable work environment to increase employee productivity and loyalty. The research method used was descriptive quantitative with a survey approach. Data were obtained through the distribution of questionnaires to respondents and analysed using multiple linear regression analysis with the help of SPSS version 25. The results showed that occupational safety and health (OSH) had a positive and significant effect on employee performance, with a regression coefficient value of 0.391. This indicates that the implementation of existing OSH procedures in the company is running well and according to procedure. Conversely, the work environment has a positive and significant effect on employee performance with a coefficient of 0.399. Simultaneously, both variables affect employee performance. The conclusion of this study is that improving employee performance at PT. Surya Toto Indonesia Tbk can be achieved through the management of a comfortable, safe, and productivity-supporting work environment, as well as the implementation of effective OSH programmes that do not hinder work processes Keywords: Occupational Safety and Health (OSH), Work Environment, Employee Performance.